Effects of smoking cessation intervention on smoking status and risk factors of cardiovascular diseases among subjects participating in the smoking cessation program - Azmi, Junainah; Nurumal, Mohd. Said; NM, Mohamad Haniki; Ab Rahman, Norny Syafinaz (Nova Science Publishers, Inc., 2019)
Background: Smoking is known as the leading cause of deaths worldwide. One individual dies every six seconds from a tobacco-related disease. This study aims to describe the demographic characteristics and smoking history of cardiovascular disease patients participating in a smoking cessation program. Subjects and Methods: An interventional study with a control and an intervention group was carried out on 65 adult cardiac patients who were smokers at the outset. The study was conducted in the Cardiac Unit, at the Hospital Tengku Ampuan Afzan (HTAA), Kuantan Pahang. A questionnaire was constructed to collect data in three different phases. A total of 65 adult patients were recruited for both the intervention and control groups. Results: Almost all of the participants started smoking during their adolescent period (mean age: 16.65 ± 3.92 years). Most of them had been smoking for the last 29 years with a mean of 29.77 ± 9.48 years. All subjects in both groups were associated with smoking, namely smokers with cardiovascular diseases (CVDs). Cessation of smoking by intensive intervention was associated with significantly greater quit attempts and decreased use of nicotine compared to the control group. The proportion of subjects stopping or reducing smoking was significantly more in the intensive intervention group than in the control group. Larger studies are needed to check on our findings. Conclusion: Intensive intervention to stop smoking by using a warning message via a video can induce fear and increase motivation resulting in a significant decline in smoking. Further studies are needed to target other groups of smokers, to find out the efficacy of this method in reducing smoking prevalence among the Malaysian CVD population, particularly younger males of Malay ethnicity.